2020
DOI: 10.1590/1981-6723.32918
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organic acids and carbohydrates in ‘Salustiana’ orange fruit from different rootstocks

Abstract: This study aimed to determine carbohydrates and organic acids in fruit from ‘Salustiana’ orange tree [Citrus sinensis (L.) Osb.] grafted onto different rootstocks using the HPLC technique, as well as to evaluate their physicochemical properties. As rootstocks, we tested ‘Rangpur’ lime, ‘Cleopatra’ mandarin, ‘Sunki’ mandarin, ‘Swingle’ citrumelo, and ‘C-13’ citrange. Fully mature fruit was first characterized according to their physicochemical parameters as fruit mass, longitudinal and equatorial diameters, pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…These reports explain why the fruits from the SM/SC combination showed a higher juice yield. Carvalho et al (2020) also found that the fruits of 'Salustiana' orange trees grafted onto SC produced more juice than those grafted onto RL. According to Domingues et al (2021), when grafted onto Poncirus trifoliata hybrid rootstocks, orange trees produced fruits with higher SS content and juice yield.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…These reports explain why the fruits from the SM/SC combination showed a higher juice yield. Carvalho et al (2020) also found that the fruits of 'Salustiana' orange trees grafted onto SC produced more juice than those grafted onto RL. According to Domingues et al (2021), when grafted onto Poncirus trifoliata hybrid rootstocks, orange trees produced fruits with higher SS content and juice yield.…”
Section: Discussionmentioning
confidence: 84%
“…The greater fruit weight produced by SM/RL at 258 DAA may be attributed to the robustness of this rootstock, as it has a deep root system that allows greater absorption of water and nutrients (Prieto et al, 2012). Heavier fruits correspond to increasingly diluted organic acids (Carvalho et al, 2020). Therefore, fruits with higher albedo and flavedo and lower juice yield will present fewer carbohydrates, acids, amino acids, and vitamins in the juice (Béber et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total acidity in sweet orange juices is mainly related to citric acid, the main organic acid present in these fruits ( Table 4 ) [ 80 , 81 ]. Organic acids are formed in the oxidative tricarboxylic acid (TCA) cycle, known as Krebs or the citric acid cycle, by the mitochondrial pathway in the juice cells [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other drinks, orange juice caused a more substantial loss of K from the tooth ( Figure 1 ). Orange juices have acids such as ascorbic acid and citric acid [ 33 ]. Beltrame et al [ 15 ], analyzing microhardness, proved that bovine enamel immersed in orange juices for 10 min, 3 times/day for 7 days, also caused a loss of enamel structure.…”
Section: Discussionmentioning
confidence: 99%